COVID-19: the Austrian experience - Heger, Florian; Moshammer, Hanns (Asian Pacific Journal of Environment and Cancer, 2020)
This short paper reports on the Austrian experiences with the Corona pandemic in the first quarter of 2020. In the beginning Austrian experts neglected the threat but a cluster in a skiing resort including international visitors served as a wake-up call and quickly after that strict and successful measures were applied. The paper proceeds describing the development of SARS-CoV-2 PCR testing and upgrading of testing facilities in Austria. The Austrian Agency for Health & Food Safety (AGES) played a leading role in this process. International cooperation and information exchange were fundamental to the successful implementation of specific and sensitive laboratory methods.